EVALUASI TOKSISITAS, AKTIVITAS ANTIBAKTERI DAN ANTIOKSIDAN KOMPONEN BIOAKTIF ROSELA DENGAN VARIASI JENIS PELARUT - Ike Sitoresmi M Purbowati, Khaswar Syamsu, Endang Warsiki, Herastuti Sri Rukmini (Department of Agroindustrial Technology, Bogor Agricultural University, 2015)
The toxicity, antibacterial and antioxidant activity of Hibiscus sabdariffa extract was investigated in thisstudy. Extraction was carried out using 70%ethanol, ethyl acetate, and hexane. Qualitative method was used todetermine the phytochemical calyx content, Brine Shrimp Lethality for toxicity test, antibacterial test was doneagainst Staphylococcus aureus and Escherichia coli were using disc diffusion method. Total antioxidant activitydetermination by the ferric thiocyanate method. The results showed that bioactive compounds in roselle calyxwere flavonoid, phenolic, tannin, alkaloid, and steroid. Seventy percent ethanol could extract higher phenolic(19.45 + 0.32 mg/g) compared to ethyl acetate and hexane, which were only extract 7.51 + 0.49 mg/g and 2.73+0.31 mg/g respectively, therefore 70% ethanol more effective compared to the other solvent. The 70% ethanolextract showed the highest activity (510.613μg/mL) compare to ethyl acetate (1241.983μg/mL) and hexane(1718.446μg/mL) respectively. Seventy percent ethanol and ethyl acetate extract also had antibacterial activity.Inhibition zone against Staphylococcus aureus 7.7 + 2.01 mm and 7.53 + 2.19 mm and against Escherichia coli13.28 + 3.30 mm, 12.35 + 3.13 mm respectively. There was no inhibitory zone for crude hexane extract. Theantioxidant activity of 70% ethanol (439.3270 μL/mL) higher than hexane (587.916μL/mL) and ethyl acetate(481.392 μL/mL).Keywords: antioxidant activity, antibacterial activity, Hibiscus sabdariffa, toxicity,